Implementasi Sistem Informasi Manajemen Nikah (SIMKAH) dalam Pencegahan Manipulasi Data Perkawinan di KUA Kecamatan Gantarangkeke Kabupaten Bantaeng: Analisis Maslaḥah - Zainuddin, Zainuddin; Jafar, Usman; Syukri, A Muhammad (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
The implementation of marriage administration digitization through the Marriage Management Information System (SIMKAH) is part of efforts to reform marriage registration governance to ensure data accuracy and integrity. However, the effectiveness of SIMKAH cannot be assessed solely from a technical-administrative perspective, but must also be analyzed within the normative framework of Islamic law. This study aims to examine the implementation of SIMKAH in preventing marriage data manipulation at the Gantarangkeke Subdistrict KUA in Bantaeng Regency using the maslaḥah perspective as the basis for analysis. The focus of the research is on ensuring the security and protection of marriage data, the impact of SIMKAH implementation on preventing data manipulation, and the operational mechanisms of SIMKAH in realizing the principle of maslahah. This study uses a qualitative method with theological, sociological, and syar'i approaches. Data were obtained through observation, in-depth interviews, and documentation, then analyzed descriptively-analytically with an emphasis on the relationship between empirical practices and normative principles of Islamic law. The results of the study show that SIMKAH provides an integrated system-based recording mechanism, automatic data validation, tiered access control, and audit trails that enable continuous administrative supervision, thereby significantly limiting the opportunities for manipulation of marriage data. The implementation of this system has had an impact on increasing the transparency, accountability, and reliability of marriage data at the KUA level. From a maslahah perspective, SIMKAH functions as an instrument for protecting the public interest (ḥifẓ al-maṣlaḥah al-‘āmmah) by preventing mafsadah in the form of data falsification and ensuring legal certainty for all parties. The novelty of this research lies in the integration of the analysis of the marriage administration information system with the maslahah framework in Islamic law. This research has implications for strengthening the policy of digitizing religious services and developing fair, accountable, and maslahah-oriented marriage registration governance.